Market Failure, Regulation and Education of Financial Advisors - Adam Steen; Dianne McGrath; Alfred Wong (Australasian Accounting, Business and Finance Journal, 2016)
This paper explores the recent series of financial scandals in the Australian financial advice industry. It examines the causes, consequences and responses to these scandals by financial institutions, investors and regulators through the lens of relevant finance theory and extant literature. Although the paper focuses on the recent Australian experience the discussion and findings presented are of relevance to financial market regulation worldwide. It is proposed that a combination of compensation, education, training and structural reforms are required to reduce the undesirable effects of information asymmetry, adverse selection and moral hazard in the finance sector.
Keywords: Financial planning scandals; financial advice; regulation; financial literacy